Hierachical epicuticular wax coverage on leaves of Deschampsia antarctica as a possible adaptation to severe environmental conditions - Gorb, Elena V.; Kozeretska, Iryna A.; Gorb, Stanislav N. (Beilstein Journal of Nanotechnology, 2022)
Using cryo scanning electron microscopy, the surface micromorphology of vegetative (leaf blade and ligule) and generative (pedicel and outer glume) organs in Deschampsia antarctica, one of the only two flowering plants native to Antarctica, was examined. Whereas the pedicel and outer glume were wax-free, both leaf sides had a prominent epicuticular wax coverage consisting of two superimposed layers: polygonal rodlets formed by fused irregular platelets (the lower wax layer) and membraneous platelets (the upper wax layer). Although the adaxial (inner) and abaxial (outer) leaf surfaces showed a similar microstructure of the wax coverage, they differed in the thickness ratio between lower and upper wax layer. The ligule bore a very loose wax coverage composed of separate scale-like projections or clusters of them. We suppose that the two-layered wax densely covering both leaf surfaces might contribute to the plant adaptation to severe environmental conditions in Antarctica due to an increase of its resistance against cold temperatures, icing, harmful UV radiation, and dehydration. The presence of the epicuticular wax on the abaxial leaf side and the ligule as well as the hierarchical structure of the wax coverage on both leaf surfaces is described in D. antarctica for the first time.
Keywords: cryo-SEM; microstructure; plant; surface; wax projection